Absorption, metabolism and excretion of [14C]pomalidomide in humans following oral administration - Hoffmann, Matthew; Kasserra, Claudia; Reyes, Josephine; Schafer, Peter; Kosek, Jolanta; Capone, Lori; Parton, Anastasia; Kim-Kang, Heasook; Surapaneni, Sekhar; Kumar, Gondi (Cancer chemotherapy and pharmacology, 2013)
Purpose To investigate the pharmacokinetics and disposition of [ 14 C]pomalidomide following a single oral dose to healthy male subjects. Methods Eight subjects were administered a single 2 mg oral suspension of [ 14 C]pomalidomide. Blood (plasma), urine and feces were collected. Mass balance of radioactivity and the pharmacokinetics of radioactivity, pomalidomide and metabolites were determined. Metabolite profiling and characterization was performed. The enzymes involved in pomalidomide metabolism and the potential pharmacological activity of metabolites were evaluated in vitro. Results Mean recovery was 88 %, with 73 and 15 % of the radioactive dose excreted in urine and feces, respectively, indicating good oral absorption. Mean C max , AUC 0−∞ and t max values for pomalidomide in plasma were 13 ng/mL, 189 ng*h/mL and 3.0 h. Radioactivity and pomalidomide were rapidly cleared from circulation, with terminal half-lives of 8.9 and 11.2 h. Pomalidomide accounted for 70 % of the circulating radioactivity, and no circulating metabolite was present at >10 % of parent compound. Pomalidomide was extensively metabolized prior to excretion, with excreted metabolites being similar to those observed in circulation. Clearance pathways included cytochrome P450-mediated hydroxylation with subsequent glucuronidation (43 % of the dose), glutarimide ring hydrolysis (25 %) and excretion of unchanged drug (10 %). 5-Hydroxy pomalidomide, the notable oxidative metabolite, was formed primarily via CYP1A2 and CYP3A4. The hydroxy metabolites and hydrolysis products were at least 26-fold less pharmacologically active than pomalidomide in vitro. Conclusions Following oral administration, pomalidomide was well absorbed, with parent compound being the predominant circulating component. Pomalidomide was extensively metabolized prior to excretion, and metabolites were eliminated primarily in urine.